Biocontrol Processes in Fruits and Fresh Produce, the Use of Lactic Acid Bacteria as a Sustainable Option - Linares-Morales, José R.; Gutiérrez-Méndez, Néstor; Rivera-Chavira, Blanca E.; Pérez-Vega, Samuel B.; Nevárez-Moorillón, Guadalupe V. (Frontiers in Sustainable Food Systems, 2018)
After harvesting fruits and vegetables and during storage and transportation, its sensorial, nutritional and sensorial quality decreases due to its high moisture content, microbial growth, environmental factors, maturity and senescence. Considering their very short shelf life, fruits and vegetables need immediate post-harvest care to increase it. The most common conservation methods are based on the control of the transpiration rate, respiration and microbial spoiling. However, traditional methods have proven to be vulnerable. Between 25 and 40% of fruits and vegetables are lost before consumption because of inadequate post-harvest treatments. In recent years, the development of alternative methods to assure microbial safety of fresh fruits and vegetables has been an important topic of investigation. Among these new methods, biopreservation using Lactic Acid Bacteria has been gaining interest, since they are classified as “generally recognized as safe” and have shown antimicrobial capacities; additionally, it is considered an environmentally friendly method. On the other hand, microencapsulation in a biodegradable matrix protects Lactic acid bacteria against unfavorable environmental conditions, which maintains their viability for a longer period. Therefore, the use of microencapsulated Lactic acid bacteria promises to be an effective technique to guarantee safety and to extend the useful life of fruits and vegetables during post-harvest. This review describes the main methods of preservation, as well as the emerging methods used to preserve fresh fruits and vegetables, with emphasis on bio-preservation as a proposal for future research.